Dolor musculoesquelético en espalda y extremidades superiores y su relación con factores ergonómicos en trabajadores de enfermería de Costa Rica y Nicaragua - Cubero-Monestel, Alejandra (Instituto Tecnológico de Costa Rica, 2017)
Introduction: The continuous increase of physical demands generated by work contributes to the increase of health problems such as musculoskeletal pain particularly in low and middle income countries. Specifically, in nursing personnel, musculoskeletal pain has been identified as an important cause of disability; and it has been suggested that ergonomic factors as repetitive motion, elbow flexion and extension can have an important role in its development. Objective: To evaluate the association of ergonomic risk factors with lower back and upper extremities musculoskeletal pain in nursing personnel from Costa Rica and Nicaragua in order to design a health surveillance program for the identification and prevention of ergonomic hazards in this occupational group. Methods: Cross-sectional investigation that included a sample of 549 nurses from hospitals in Costa Rica and Nicaragua from the baseline questionnaire of the Cultural and Psychosocial Influences on Disability(CUPID) study. Prevalence was calculated for lower back and upper extremities musculoskeletal pain according to socio-demographic characteristics, labor conditions, psychosocial and ergonomic risks (i.e. hand, wrist and finger repetitive motion, elbow flexion and extension for prolonged time, work with hands above the shoulders, lifting loads over 25kg). Multivariate Poisson regression models were made to estimate prevalence ratios (PR) and their 95% confidence intervals for each of the ergonomic risk factors. Results: Higher prevalence was observed in women than in men for the 3 pain classifications studied for lower back and upper extremities. Lower back musculoskeletal pain prevalence was in general higher for all the ergonomic risk factors; especially for lifting loads over 25kg (between 77% y 41,7%). Adjusted PRs show significant differences between work with hands above the shoulders and lifting loads over 25kg in the lower back zone (PR=1.8 IC95% 1.2-2.5; 1.8 IC 95% 1.3-2.7; 1.5 IC95% 1.1-2.1) as well as upper extremities PR=1.4 IC 95% 1.1-1.9; 1.4 IC95% 1.0-2.1; 1.4 IC 95% 1.0-1.9). Conclusions: This study identified relatively high musculoskeletal pain prevalence in nursing workers from Costa Rica and Nicaragua, as well as important associations with ergonomic risk factors. As this is the first investigation in the Central American region that examines this association, it is important to replicate it’s findings with additional investigation. The results suggest that hospitals should integrate preventive actions with a focus on ergonomic factors to reduce the risk of musculoskeletal pain in workers.
Resultados del estudio: Internacional Cultural and Psychosocial Influences on Disability (CUPID)
Proyecto de Graduación (Maestría en Ingeniería en Seguridad Laboral e Higiene Ambiental) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Seguridad Laboral e Higiene Ambiental, Universidad Nacional, Instituto Regional de Estudios en Sustancias Tóxicas, 2017.
Keywords: Seguridad ocupacional; Factores de riesgo; Hospitales; Enfermería; Condiciones de trabajo; Ergonomía